1982
DOI: 10.1073/pnas.79.12.3798
|View full text |Cite
|
Sign up to set email alerts
|

Base sequence of a cloned snake W-chromosome DNA fragment and identification of a male-specific putative mRNA in the mouse.

Abstract: A 2.5-kilobase fragment of a sex-specific satellite DNA from the Colubrid snake species Elaphe radiata has been cloned, and its sequence has been determined. It contains 26 and 12 copies, respectively, of two base quadruplets, G-A-T-A and G-A-C-A, as its sole highly repetitious elements. Southern hybridization experiments with genomic DNA ofthe chicken, the mouse, and man indicated male sex-specific conservation of at least parts of this cloned DNA. In situ hybridization experiments with metaphase chromosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…There could be other sequences with ability to form Z-DNA in vivo. Other types ofsimple repetitive sequence such as (T-C)n and (G-A-T-A)n have been reported in cloned genes (31,32). Furthermore, a high copy number of poly(dG)poly(dC) sequence was detected by hybridization in the calf and chicken genomes but many fewer in human and mouse genome (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…There could be other sequences with ability to form Z-DNA in vivo. Other types ofsimple repetitive sequence such as (T-C)n and (G-A-T-A)n have been reported in cloned genes (31,32). Furthermore, a high copy number of poly(dG)poly(dC) sequence was detected by hybridization in the calf and chicken genomes but many fewer in human and mouse genome (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the first element, it was initially discovered by Epplen et al (1982), and several subsequent studies showed that this sequence is conserved in different species, including humans (Srivastava et al, 2008), and seems to be associated to sex determination and evolution of sex chromosomes in snake groups (Jones & Singh, 1985). Although no sex chromosome system has been described in Auchenipteridae, this highly dispersed sequence found in A. inermis is a new factor to the group, which must be further exploited in other species.…”
Section: Discussionmentioning
confidence: 99%
“…The Banded krait minor satellite (Bkm) sequerices are present in the heterogametic sex of many vertebrates, e.g. on the W chromosome of birds (Jones and Singh 1985) and the Y chromosome of the mouse (Epplen et al 1982;Singh et al 1984). A considerable part of this satellite sequence consists of particular simple repetitive sequences, (gata)n and (gaca)m, which are present in a wide range of vertebrates (Epplen 1988).…”
Section: Introductionmentioning
confidence: 99%